To care or not to care - reflections on the ethics of blended learning in times of disruption - Swartz, B.C.; Gachago, D.; Belford, C. (South African Journal of Higher Education, 2018)
The recent student protests in South African Higher Education have highlighted both the opportunities and challenges of blended/online learning in higher education. This paper describes two lecturers’ attempts at continuing teaching online during the 2016 campus closure at a large University of Technology in South Africa. Using Tronto’s Ethics of Care lens and in particular her moral characteristics of care, namely attentiveness, responsibility, competence, responsiveness and solidarity, we reflect on the ethics of our practices when moving towards more open educational practices. Recommendations on academic staff development that promotes ethical open practices conclude the paper.